A mm-Wave 2D Ultra-Wideband Imaging Radar for Breast Cancer Detection - Stefano Moscato; Giulia Matrone; Marco Pasian; Andrea Mazzanti; Maurizio Bozzi; Luca Perregrini; Francesco Svelto; Giovanni Magenes; Paolo Arcioni; Paul Summers (International Journal of Antennas and Propagation)
This paper presents the preliminary design of a mm-wave ultra-wideband (UWB) radar for breast cancer detection. A mass screening of women for breast cancer is essential, as the early diagnosis of the tumour allows best treatment outcomes. A mm-wave UWB radar could be an innovative solution to achieve the high imaging resolution required without risks for the patient. The 20–40 GHz frequency band used in the system proposed in this work guarantees high cross/range resolution performances. The developed preliminary architecture employs two monomodal truncated double-ridge waveguides that act as antennas; these radiators are shifted by microstep actuators to form a synthetic linear aperture. The minimum antenna-to-antenna distance achievable, the width of the synthetic aperture, and the minimum frequency step determine the performance of the 2D imaging system. Measures are performed with a mm-wave vector network analyzer driven by an automatic routine, which controls also the antennas shifts. The scattering matrix is then calibrated and the delay-multiply-and-sum (DMAS) algorithm is applied to elaborate a high-resolution 2D image of the targets. Experimental results show that 3 mm cross and 8 mm range resolutions were achieved, which is in line with theoretical expectations and promising for future developments.